Is There a Preferential Treatment for Locals in the Labor Market? Evidence from Takeovers - Tommaso Colussi; Livio Romano (Institute of Labor Economics (IZA), 2016)
This work analyzes the extent to which local social networks affect workers' labor market outcomes and firms' economic performance. By exploiting variations in firms' ownership generated by takeovers, we find that belonging to the same community of origin as the new employer significantly increases an employee's job retention probability. Finally, we show that the share of local employees retained after the takeover is negatively associated with the probability of closure of the acquiring firm.
Keywords: D22; J24; J63; J7; 330; takeovers; local social networks; social capital; firm behavior